An application of Saddlepoint approximation for period detection of stellar light observations. Issue 1 (20th February 2023) - Derezea, Efthymia; Kume, Alfred; Froebrich, Dirk
Abstract: One of the main features of interest in analysing the light curves of stars is the underlying periodic behaviour. The corresponding observations are a complex type of time series with unequally spaced time points. The main tools for analysing these type of data rely on the periodogram-like functions constructed with a desired feature so that the peaks indicate the presence of a potential period. We explore a particular periodogram for the irregularly observed time series. We identify the potential periods by implementing the saddlepoint approximation, as a faster and more accurate alternative to the simulation based methods that are currently used. The power analysis of the testing methodology is reported together with applications using light curves from the Hunting Outbursting Young Stars citizen science project.